Obiektywizacja i subiektywizacja języka w narracji dziennikarskiej - Lizisowa, Maria Teresa (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The article presents an analysis of a text selected from Rzeczpospolita daily newspaper, conducted from the standpoint of the theory of language. The author formulated a thesis that the theoretical assumptions of linguistics within the scope of communicology can be employed to assess the accuracy of information as well as journalistic writing. She carried out a linguistic interpretation of the semantic and the subjective function of language in the text. Quoting the selected excerpts, she reinterpreted the journalistic statement in direct speech acts and also gave some examples of decoding indirect speech acts, according to the theory of conversational implicatures. The author recapitulated that the use of language as a tool for communicating social facts to the readers of the press, which is typical for the idiolect of a journalist as well as for the principals of the technique of a given journalistic genre, and which is so broadly presented in the works of media specialists and theoreticians of communication, has its origin in a subtle semantic analysis of the true and false proposed by John Langshaw Austin as well as in the cooperative principles for conversation participants proposed by Herbert Paul Grice.